Do Inflation Targeting Really Reduced Exchange Rate Pass-through? - Salsa Dilla; Noer Azam Achsani; Lukytawati Anggraeni (International Journal of Economics and Financial Issues, 2017)
Implementation of inflation targeting framework (ITF) on the behavior of exchange rate pass-though (ERPT) has been an important role in the last decade. A lot of countries have changed their exchange rate regimes and monetary policy framework. As the ITF being adopted, the role of exchange rate in influencing the inflation rate has decreased. The purpose of this research is to analyze the dynamics of ERPT before and after the implementation of ITF using data from countries. We also compare the results between high income countries and middle income countries. Using autoregressive distributed lag model for 19 countries (8 high income countries; 11 middle income countries), the finding showed mixed results regarding there is a reduction of ERPT after the adoption of ITF. On average, loss of pass-through happened both for high income and middle income countries. However, there was a significant difference on the average long-run ERPT - before and after ITF implementation - in middle income countries compared to high income countries. Thus, the adoption of ITF right after crises brought greater effect to price stability in middle income countries. New empirical findings were found, particularly from middle income countries, where there is a decrease in ERPT after the adoption of ITF in Indonesia and Thailand both in the short-run and in the long-run.